The impact of stress on students’ academic performance - Akanpaadgi, Emmanuel; Binpimbu, Felicia; Kuuyelleh, Esmond Naalu (S&Co Publishing, 2023)
This study assessed the impact of stress on the academic performance of students in the Bolgatanga Technical University. It investigated the causes of stress, the symptoms of stress, the effects of stress and how students can overcome stress. The quantitative research strategy was used for the study. The research data collection was preceded by a literature review to provide an in-depth understanding of the research topic. A structured questionnaire designed in the form of a Likert-Scale was administered to One Hundred and Forty (140) students who were the participants of the study. The data was analysed using the Statistical Package for Social Sciences (SPSS) and the results were presented in the form of descriptive statistics using the Relative Importance Index (RII). The study revealed that several factors namely high cost of living, poor time management, limited facilities, difficult relations and the workload caused stress among students of the Bolgatanga Technical University. It was concluded that stress has a negative impact on the academic performance of students. The study recommends that the guidance and counselling department of the university should be strengthened to make it more effective in supporting students to overcome stress. In addition, guidance programmes such as seminars and public lectures on stress awareness should be organized periodically for students so that they can be adequately equipped with the needed skills to handle issues related to academic stress better. Finally, provision should be made in the curriculum for adequate time for students to rest by not allowing lectures to extend to weekends.